2004
DOI: 10.1023/b:qure.0000021687.18783.d6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of life in schizophrenia: Relationships to sleep quality

Abstract: We examined the relationship between perceived quality of life (QOL) and subjective quality of sleep among schizophrenia patients, and its relation to symptom severity, side effects and emotional distress. One hundred and forty five schizophrenia patients were comprehensively evaluated with standardized measures of symptom severity, adverse effects, emotional distress, QOL, and sleep quality (the Pittsburgh Sleep Quality Index, PSQI). Partial correlation and multiple regression analyses were performed. Poor sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
64
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 43 publications
15
64
1
2
Order By: Relevance
“…The first type of factors was derived by analysis on both cross-sectional [10,[38][39][40] and current longitudinal data. They include opposite factors with distressing (severity of symptoms, distress, side effects, insight, poor sleep quality, emotion coping, repeated suicide attempts, harm avoidance) and protective (task and avoidance coping styles, social support, selfefficacy, self-esteem) effects on QOL level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first type of factors was derived by analysis on both cross-sectional [10,[38][39][40] and current longitudinal data. They include opposite factors with distressing (severity of symptoms, distress, side effects, insight, poor sleep quality, emotion coping, repeated suicide attempts, harm avoidance) and protective (task and avoidance coping styles, social support, selfefficacy, self-esteem) effects on QOL level.…”
Section: Discussionmentioning
confidence: 99%
“…This model postulated that subjective QOL is an outcome of the interaction of an array of distress factors, on the one hand, and protective factors, on the other, and suggests that satisfaction with QOL decreases if distress/clinical factors outweigh protective factors, and vice versa. The DP model was applied for analysis of relationships between QOL levels and major psychoses [10,36], schizophrenia [37], side effects of antipsychotic agents [17], coping styles [22], temperament factors [38], suicide behavior [39], and sleep quality [40].…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality correlates inversely with quality of life in psychiatric populations even after correcting for adverse drug effects 17,18 . The true incidence of sleep apnoea and in particular the obstructive sleep apnoea syndrome in those with long term mental health problems maintained on psychotropic medication is unclear with few systematic studies of community cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite service users emphasising the importance of functioning in their recovery (Wood, Price, Morrison, & Haddock, 2011). Indeed, research has shown that sleep disturbance is associated with impaired quality of life (QoL) and coping in people experiencing psychosis (Ritsner, Kurs, Ponizovsky, & Hadjez, 2004;Hofstetter, Lysaker, & Mayeda, 2005). Neuropsychological findings also demonstrate that sleep disturbance contributes to impaired performance on tasks of sustained 4 attention (Forest et al, 2007), executive functioning (Keshavan, Cashmere, Miewald, & Yeragani, 2004) and IQ (Manoach et al, 2014).…”
mentioning
confidence: 99%